Oral Tori in Chronic Peritoneal Dialysis Patients. - Chia-Lin Hsu; Ching-Wei Hsu; Pei-Ching Chang; Wen-Hung Huang; Cheng-Hao Weng; Huang-Yu Yang; Shou-Hsuan Liu; Kuan-Hsing Chen; Shu-Man Weng; Chih-Chun Chang; I-Kuan Wang; Aileen I Tsai; et al. (PLoS ONE, 2016)
The pathogenesis of oral tori has long been debated and is thought to be the product of both genetic and environmental factors, including occlusal forces. Another proposed mechanism for oral tori is the combination of biomechanical forces, particularly in the oral cavity, combined with cortical bone loss and trabecular expansion, as one might see in the early stages of primary hyperparathyroidism. This study investigated the epidemiology of torus palatinus (TP) and torus mandibularis (TM) in peritoneal dialysis patients, and analyzed the influences of hyperparathyroidism on the formation of oral tori.In total, 134 peritoneal dialysis patients were recruited between July 1 and December 31, 2015 for dental examinations for this study. Patients were categorized into two subgroups based on the presence or absence of oral tori. Demographic, hematological, biochemical, and dialysis-related data were obtained for analysis.The prevalence of oral tori in our sample group was high at 42.5% (57 of 134), and most patients with oral tori were female (61.4%). The most common location of tori was TP (80.7%), followed by TP and TM (14.0%), then TM (5.3%). All 54 TP cases were at the midline, and most were <2 cm (59.3%), flat (53.7%), and located in the premolar region (40.7%). Of the 11 TM cases, all were bilateral and symmetric, mostly <2 cm (81.9%), lobular (45.4%), and located at premolar region (63.6%). Interestingly, patients with oral tori had slightly lower serum levels of intact parathyroid hormones than those without oral tori, but the difference was not statistically significant (317.3±292.0 versus 430.1±492.6 pg/mL, P = 0.126). In addition, patients with oral tori did not differ from patients without tori in inflammatory variables such as serum high sensitivity C-reactive protein levels (6.6±8.2 versus 10.3±20.2 mg/L, P = 0.147) or nutritional variables such as serum albumin levels (3.79±0.38 versus 3.77±0.45 g/dL, P = 0.790). Furthermore, there were no differences between patients with and without oral tori in dialysis adequacy (weekly Kt/Vurea, 2.14±0.39 versus 2.11±0.33, P = 0.533; weekly creatinine clearance rate, 59.31±17.58 versus 58.57±13.20 L/1.73 m2, P = 0.781), or peritoneal membrane transporter characteristics (P = 0.098).Secondary hyperparathyroidism does not contribute to the formation of tori in peritoneal dialysis patients. Further studies are warranted.